2016
DOI: 10.1002/cam4.836
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aerobic exercise on levels of IL‐4 and IL‐10: results from two randomized intervention trials

Abstract: The mechanisms whereby regular exercise reduces chronic inflammation remain unclear. We investigated whether regular aerobic exercise alters basal levels of interleukin (IL)‐10 and IL‐4 in two randomized trials of physical activity. The Alberta Physical Activity and Breast Cancer Prevention Trial (ALPHA, n = 320) and the Breast Cancer and Exercise Trial in Alberta (BETA, n = 400) were two‐center, two‐armed randomized trials in inactive, healthy, postmenopausal women. Both trials included an exercise interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 65 publications
(134 reference statements)
0
24
0
Order By: Relevance
“…After deleting duplicates, two reviewers (PTQ and RX) screened titles and abstracts and excluded unrelated records. Finally, 122 full-text articles were examined for eligibility, and 12 studies met the inclusion criteria (Bergström et al, 2009; Muscari et al, 2010; Tartibian et al, 2011, 2015; Friedenreich et al, 2012; Irwin and Olmstead, 2012; Nishida et al, 2015; Abdollahpour et al, 2016; Alghadir et al, 2016; Conroy et al, 2016; Sbardelotto et al, 2017; Mohammadi et al, 2018). One of these 12 studies (Sbardelotto et al, 2017) was excluded, as data remained unavailable, despite attempts to contact the original author.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After deleting duplicates, two reviewers (PTQ and RX) screened titles and abstracts and excluded unrelated records. Finally, 122 full-text articles were examined for eligibility, and 12 studies met the inclusion criteria (Bergström et al, 2009; Muscari et al, 2010; Tartibian et al, 2011, 2015; Friedenreich et al, 2012; Irwin and Olmstead, 2012; Nishida et al, 2015; Abdollahpour et al, 2016; Alghadir et al, 2016; Conroy et al, 2016; Sbardelotto et al, 2017; Mohammadi et al, 2018). One of these 12 studies (Sbardelotto et al, 2017) was excluded, as data remained unavailable, despite attempts to contact the original author.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 RCTs involving 1,250 participants (188 males and 1,062 females, age range 40–95 years) were included in the review. The styles of aerobic exercise utilized in the intervention groups were diverse, involving Tai Chi (Irwin and Olmstead, 2012), treadmill (Mohammadi et al, 2018), bench step exercises (Nishida et al, 2015), and multicomponent aerobic exercises (Bergström et al, 2009; Muscari et al, 2010; Tartibian et al, 2011, 2015; Alghadir et al, 2016); three studies (Friedenreich et al, 2012; Abdollahpour et al, 2016; Conroy et al, 2016) did not describe a specific exercise style. The duration of the exercise phase in the included studies ranged from 2 to 12 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the increase of IL-1ra after the interventions could perhaps indicate that the resistance exercise was of high enough intensity to increase its production. Results from two large randomized aerobic exercise intervention trials suggest that aerobic exercise does not alter IL-10 or IL-4 [ 63 ], which if so may explain why IL-1ra was the only anti-inflammatory cytokine that had increased. However, there were no changes in proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…A similar variability of results is also found for the anti-inflammatory cytokine IL-10 for BC patients, although in other cancers, according to a meta-analysis of 21 studies [63], this IL has been reported to be associated with worse outcome. In addition, and in contrast to IL-6, IL-10 is not modulated in BC patients by physical exercise [64].…”
Section: Discussionmentioning
confidence: 99%